Multiple Morphometric Assessment of Microglial Cells in Deafferented Spinal Trigeminal Nucleus - García-Magro, Nuria; Martin, Yasmina B.; Palomino-Antolin, Alejandra; Egea, Javier; Negredo, Pilar; Avendaño, Carlos (Frontiers in Neuroanatomy, 2020)
Microglia (MG) are the first cells to react to the abnormal incoming signals that follow an injury of sensory nerves and play a critical role in the development and maintenance of neuropathic pain, a common sequel of nerve injuries. Here we present population data on cell number, soma size, and length of processes of MG in the caudal division of the spinal trigeminal nucleus (Sp5C) in control mice and at the peak of microgliosis (7 days) following unilateral transection of the infraorbital nerve (IoN). The study is performed combining several bias- and assumption-free imaging and stereological approaches with different immunolabeling procedures, with the objective of tackling some hard problems that often hinder proper execution of MG morphometric studies. Our approach may easily be applied to low-density MG populations, but also works, with limited biases, in territories where MG cell bodies and processes form dense meshworks. In controls, and contralaterally to the deafferented side, MG cell body size and shape and branching pattern matched well the descriptions of “resting” or “surveillant” MG described elsewhere, with only moderate intersubject variability. On the superficial laminae of the deafferented side, however, MG displayed on average larger somata and remarkable diversity in shape. The number of cells and the length of MG processes per mm3 increased 5 and 2.5 times, respectively, indicating a net 50% decrease in the mean length of processes per cell. By using specific immunolabeling and cell sorting of vascular macrophages, we found only a negligible fraction of these cells in Sp5C, with no differences between controls and deafferented animals, suggesting that blood-borne monocytes play at most a very limited role in the microgliosis occurring following sensory nerve deafferentation. In sum, here we present reliable morphometric data on MG in control and deafferented trigeminal nuclei using efficient methods that we propose may equally be applied to any morphometric population analysis of these cells under different physiological or pathological conditions.